Tendencias en el uso del biocarbón como acondicionador de suelos - Aponte, Gloria María (2021)
Biochar is a product that is obtained from different types of biomass such as pine wood bark, bamboo, organic and vegetable waste, human manure, poultry manure, among others. Biochar has been used in different ways as a soil improver among which are: improving the retention of water and nutrients in the soil, increasing the productivity of crops, increasing the quality of the soil and also acting as a sequestrant of carbon dioxide. This use as a soil improver is not only recognized from a research or academic point of view, but there is a lot of business interest in its development and commercialization, which is seen by the accelerated trend of patent research and development in the last ten years. Technology leadership is represented by US companies and the academic sector by Chinese universities publications. The future of biochar, as a soil conditioner, looks promising from both a business and academic point of view.